The Effectiveness of Cooperative Learning Model with Group Investigation (Gi) Using Comic Media Towards Mathematical Literacy Ability of Viii Students at SMP Negeri 1 Punggelan - Khasanah, Nur; Setiaji, Heru Agni (International Journal of Research in Mathematics Education, 2023)
This study aims to determine the effectiveness of the GI-type cooperative learning model assisted by comic media on increasing the mathematical literacy skills of class VIII students of SMP Negeri 1 Punggelan. This research is an experimental research with a quantitative approach. The population in this study were students of class VIII SMP Negeri 1 Punggelan and the samples used were taken by simple random sampling technique and the sample results obtained were students of class VIII G and class VIII H, totaling 58 students. The instrument used in this study was a description test consisting of a pretest and a posttest. The results of this study are that the average mathematical literacy ability of students who are subjected to the GI type cooperative learning model assisted by comic media is better than those who are not subjected to it, as seen from the results of the N-Gain test, namely the experimental class obtained an average N-Gain value of 0 .77 with high criteria, while in the control class the average N-Gain value for the control class was 0.47 with moderate criteria. In the t-test, the two independent samples showed a significance result of 0.000 <0.05, meaning that there was a significant difference in students' mathematical literacy skills between the experimental and control classes. The GI type cooperative learning model assisted by comic media was declared effective for increasing mathematical literacy skills with the average N-Gain test results obtained in the experimental class by 77% with effective criteria and in the control class by 47% with less effective criteria.